Analisis Pengaruh Intensitas dan Ukuran Tetesan Hujan terhadap Kinerja Piezoelektrik pada Pemanfaatan Curah Hujan menjadi Energi Listrik - M. Ravi Cahya Firdaus; Rifky (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
The increasing demand for energy encourages the development of renewable energy sources, but the utilization of rain energy in Indonesia is still limited. This literature study examines the effect of rainfall intensity and water droplet size on the electrical output of polycarbonate piezoelectrics. The intensity variation is set at less than 5 mm/hour (light rain), 5-20 mm/hour (moderate rain) and 20-50 mm/hour (heavy rain), with droplet sizes of 2.5 mm, 5 mm, and 7.5 mm. The experimental method in this study was carried out by comparing the differences in rainfall intensity and the size of raindrops that fell on the roof that had been installed with a piezoelectric. The raw data measured were voltage and electric current. The results of data processing are in the form of piezoelectric performance, namely electrical power and efficiency. A review of the variations in rainfall intensity and raindrop size shows a relationship between the kinetic energy of the droplets and the piezoelectric output voltage.